The idiot - Dostoyevsky, Fyodor, 1821-1881.; Martin, Eva. ([Auckland, N.Z.] : Floating Press, 2009)
Prince Myshkin, a good yet simple man, is out of place in the corrupt world created by Russia's ruling class.
eBooks on EBSCOhost
Keywords: Princes -- Russia -- Fiction; Good and evil -- Fiction; Triangles (Interpersonal relations) -- Fiction; Russia (Federation) -- Social conditions -- 1801-1917 -- Fiction; Princes -- Russie -- Romans, nouvelles, etc; Triangle (Relations humaines) -- Romans, nouvelles, etc; Good and evil; Princes; Social conditions; Triangles (Interpersonal relations); Russia; Russia (Federation); 1801-1917; Fiction